Multi-photon decay mode spectroscopy of positronium - Johnson, Storm (Department of Physics, 2022)
An approximation for the branching ratio of the four-photon decay of parapositronium (BR4γ) was measured using a multi-gamma-ray spectrometer. For the first time in such measurements, the spectrometer consisted of an array of eight identical LaBr3:Ce scintillator detectors, each of which combines good energy resolutions (5% and 10% at 511 keV for the signals from the eighth dynode and anode of the photomultiplier tube, respectively) with an excellent timing resolution (∼ 300 ps). These energy resolutions were minimised through an optimal selection of the digital signal processing parameter settings. The detectors were situated in a planar geometry, where the source-to-detector distance of the detector system was selected such that the effect of peak pulse pile-up was minimised (to less than 3%), while maximising the full-energy peak detection efficiency at 511 keV (to 3%). For this work, locally-produced 22Na radioactive sources were used as positron emitters, which enabled the formation of positronium and subsequent gamma decays. Energy calibration measurements were performed using a 152Eu source, where the prominent energy peaks of (121.8, 244.7, 344.3, 778.9, 964.1, 1408.0) keV were used for calibration. For the BR4γ measurement, 5×1011 events were accumulated over a measurement period of 60 days, which resulted in low statistical uncertainties for the coincident counting between detector pairs (less than 1%). Through simplifying assumptions that neglected the background corrections and efficiency normalisations for each of the 2γ and 4γ decays, a first order approximation of BR4γ was determined as the ratio between measured 4γ events (N4γ) and measured 2γ events (N2γ), such that BR4γ ∼ N4γ N2γ = 4.8 (19) × 10−7. This measured value of BR4γ differs from previous measurements and accepted literature values by a factor of 3.